Over-taxation by inflation : a study of the effects of inflation on taxation and government expenditure, and of its correction by indexing - Morgan, David R. (London : Institute of Economic Affairs, 1977)
The author revised his calculations in the light of the March 19777 Budget and indicated the implications for the analysis in his Hobart Paper in this edition.
Includes bibliographical references.
oif 26/02/2019
Loans
Keywords: Taxation; Expenditures, Public--Effect of inflation on; Indexation (Economics); Taxation--Effect of inflation on; Inflation (Finance); Great Britain